A New Generation of Activated Carbon Adsorbent Microstructures - Ethan Grigor; Joseph Carver; Edric Bulan; Stuart Scott; YM John Chew; Semali Perera (Advanced Science)
Abstract This work presents the successful manufacture and characterization of bespoke carbon adsorbent microstructures such as tessellated (TES) or serpentine spiral grooved (SSG) by using 3D direct light printing. This is the first time stereolithographic printing has been used to exert precise control over specific micromixer designs to quantify the impact of channel structure on the removal of n‐butane. Activated microstructures achieved nitrogen Brunauer Emmett Teller (BET) surface areas up to 1600 m2 g−1 while maintaining uniform channel geometries. When tested with 1000 ppm n‐butane at 1 L min−1, the microstructures exceeded the equilibrium loading of commercial carbon‐packed beds by over 40%. Dynamic adsorption breakthrough testing using a constant Reynolds number (Re 80) shows that complex micromixer designs surpassed simpler geometries, with the SSG geometry achieving a 41% longer breakthrough time. Shorter mass transfer zones were observed in all the complex geometries, suggesting superior kinetics and carbon structure utilization as a result of the micromixer‐based etched grooves and interlinked channels. Furthermore, pressure drop testing demonstrates that all microstructures had half the pressure drop of commercial carbon‐packed beds. This study shows the power of leveraging 3D printing to produce optimized microstructures, providing a glimpse into the future of high‐performance gas separation.